All Days 1996
DOI: 10.2118/35131-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Validated Hydraulic Model Predictions Give Guidelines for Optimal Annular Flow in Slimhole Drilling

Abstract: Accurate prediction of annular flow is of primary importance in slimhole drilling. A model was developed that better represents actual amular configurations. It accounts for axial variations of drillpipe eccentricity and for effeets arising from drillpipe rotation. The model is validated with data obtained from 3 industrial slimhole wells (4''3/4 and 3"3/8 phases). Based on model predictions, guidelines are given to define flow parameters and to adapt fluid rheology in order to obtain optimal hole cleaning und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to Cartalos and Song et al, 10,13 the drill column rotation, drill column eccentricity, and drill column joint size significantly affect the pressure dissipation in HW‐SH. However, their study was based only on indoor experiments ignoring temperature and pressure, that have a strong influence on the drilling fluid density and rheology.…”
Section: Numerical Model Of the Coupled Temperature‐pressure Field In...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Cartalos and Song et al, 10,13 the drill column rotation, drill column eccentricity, and drill column joint size significantly affect the pressure dissipation in HW‐SH. However, their study was based only on indoor experiments ignoring temperature and pressure, that have a strong influence on the drilling fluid density and rheology.…”
Section: Numerical Model Of the Coupled Temperature‐pressure Field In...mentioning
confidence: 99%
“…In both laminar and turbulent flows, the annular pressure dissipation tended to decrease gradually as the eccentricity of the drilling column increased. After analyzing a large amount of field and experimental data, Cartalos 13 concluded that the annular pressure depletion in HW‐SH could not be predicted accurately, even though the drilling column rotation was considered. In addition to considering the drilling column rotation, he also considered the effect of the eccentricity of the drilling column and the variability of its eccentricity along the wellbore axial direction on the annular pressure dissipation and developed a new model for the annular pressure dissipation in HW‐SH.…”
Section: Introductionmentioning
confidence: 99%
“…where DP b is bit pressure drop, Q is volumetric displacement, r m is density of drilling fluid, d 1 , d 2 , d 3 are nozzle diameters of bit. Drill string rotation factor is changed as Taylor number and Reynolds number; the Taylor number is described as follows 33,34 Ta = r(D h À D p ) n + 0:5 D p 1:…”
Section: Authors Notementioning
confidence: 99%
“…Due to the fact that a fluid flowing in the annulus of a bighole well where the annular clearance is big and the annular mud velocity is low, not similar to that of the conventional wellbore's, the calculations and technology of hydraulics suitable for conventional drilling do not show a good agreement any more. This fact implies the necessity of analysis annular mud velocity,drill pipe rotation speed that cause the variation of pressure losses in annular space to predict the fluxion of helical flow and debris migration in the annular space.R.C.McCann [1],U.Cartalos [2]and Wanghaige [3] analyze the pressure loss of a fluid flowing in the narrow annulus of a slimhole well through numerical simulation and laboratory studies, but scholars seldom study annular pressure loss in largesize deepwater drilling rise, this paper has discussed annular pressure loss in largesize deepwater drilling riser using numerical simulation.…”
Section: Introductionmentioning
confidence: 99%